2022
DOI: 10.1007/s00520-022-06914-w
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in quality of life, social distress and employment outcomes in Australian cancer survivors

Abstract: Purpose To examine how socio-demographic, comorbidities and information needs influence quality of life (QoL) outcomes of survivors of breast, colorectal, or prostate cancer, non-Hodgkin lymphoma or melanoma. Methods Cross-sectional postal survey with eligible participants identified through a population-based cancer registry. QoL outcomes were assessed by EQ-5D-5L, social difficulties index (SDI) and, for those employed at diagnosis, current employment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Consistent with results of previous studies, we found shorter education to be associated with an increased risk of impaired physical function, fatigue, and pain in cancer survivors 8,9,11,15,16 . For example, one study among 2235 breast cancer survivors reported that survivors from a lower social class had an OR of 1.7 to report poor physical function 15 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with results of previous studies, we found shorter education to be associated with an increased risk of impaired physical function, fatigue, and pain in cancer survivors 8,9,11,15,16 . For example, one study among 2235 breast cancer survivors reported that survivors from a lower social class had an OR of 1.7 to report poor physical function 15 .…”
Section: Discussionsupporting
confidence: 90%
“…In addition to these classical risk factors for poor HRQoL, some studies have suggested that socioeconomic factors, e.g., living in a disadvantaged area, 15,16 or having a low socioeconomic position (SEP) 8,9,11 are associated with poorer HRQoL but these are limited by few participants 8,9 and non-cancer specific measures of HRQoL. 11,16 Only one of these studies investigated the association between SEP and HRQoL in a nationally representative sample of cancer survivors but the study only included 2235 survivors after breast cancer. 15 We need large population-based data to explore the association between SEP indicators such as educational level and HRQoL among cancer survivors across major cancer sites, for both short-and long-terms survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, generalisability of the results will be limited to similar healthcare and costing and funding models and similar populations. For example, a smaller proportion of participants received concessional payments compared with the general public, possibly reflecting a more affluent study population, particularly given evidence of inequalities in access to clinical trials [ 110 ] and cancer care more broadly in Australia [ 111 , 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even within a universal healthcare system, many cancer patients and families experience financial hardship and emotional distress (Fitch et al, 2021(Fitch et al, , 2022. Socioeconomic status has become a prominent factor that affects the quality of life of cancer patients across disease types, with poorer socioeconomic status associated with poorer quality of life (Mon et al, 2020;Robinson et al, 2021;Su et al, 2019;White et al, 2022).…”
Section: Introductionmentioning
confidence: 99%